Language, discourse, and borders in the Yugoslav successor states - Busch, Brigitta, 1955-; Kelly-Holmes, Helen, 1968- (Current Issues in Language and Society Monographs, 2004)
Do languages create borders or do borders create languages? The contributors focus on the political transition in southeastern Europe and situate the debate on language policy in the region within the context of a wider sociological discussion of the issue of borders and the formation of national identities.